Pengembangan multimedia interaktif untuk mata pelajaran dasar desain grafis siswa SMK - Maulidia, Suci (Maliki Interdisciplinary Journal, 2024)
This study discusses the technological advancements in the educational context, focusing on the development of interactive multimedia for the basic graphic design subject in vocational high schools (SMK). The current era’s technological progress has brought about significant innovations in electronic devices and technology, influencing various aspects of life, including education. However, educational challenges persist, particularly in adapting traditional teaching approaches to align with technological advancements. Technology-based learning media, such as interactive multimedia, have the potential to enhance the effectiveness of education in more engaging and profound ways. This research designs and develops interactive multimedia for the basic graphic design subject in SMK, utilizing CorelDRAW X7 and Adobe Flash software. The interactive multimedia encompasses learning materials, profiles, and quizzes. The objective is to facilitate students in comprehending fundamental graphic design concepts through a more interactive and engaging approach. In the development of this interactive multimedia, Adobe Flash software is employed to produce multimedia elements such as images, animations, and videos. The outcome of this study is an interactive multimedia product that can be used by SMK students to better understand the basics of graphic design through the utilization of technology. This interactive learning medium is expected to enhance students’ learning motivation and assist them in gaining a better understanding of the taught concepts. By harnessing interactive multimedia intelligently, education can be transformed into a more engaging and interactive process for students.